Multiscale Computational Fluid Dynamics Modeling: Parallelization and Application to Design and Control of Plasma-Enhanced Chemical Vapor Deposition of Thin Film Solar Cells - Crose, Marquis Grant (ProQuest Dissertations & Theses, 2018)
Today, plasma-enhanced chemical vapor deposition (PECVD) remains the dominant processing method for the manufacture of silicon thin films due to inexpensive production and low operating temperatures. Nonetheless, thickness non-uniformity continues to prevent the deposition of high quality thin film layers across large wafer substrates; thickness deviations up to 20% are typical for 200 mm and above wafers. Regardless of industry, be it solar cell production or microelectronic devices, the demand for densely packed die with high quality creates a need for improved modeling and operational strategies. Over the past two decades, a number of research groups have built microscopic models for thin film growth, as well as macroscopic reactor models to approximate the gas phase reaction and transport phenomena present within PECVD systems. Unfortunately, many of the proposed modeling and simulation techniques have been overly simplified in order to reduce computational demands, or fail to capture both the macro- and microscopic domains simultaneously. In order to address persistent issues related to thickness non-uniformity in silicon processing, advanced multiscale models are needed. Motivated by these considerations, novel reactor modeling and operational control strategies are developed in this dissertation. Specifically, a macroscopic reactor scale model is presented which captures the creation of a radio frequency (RF) plasma, transport throughout the reactor domain, and thirty-four dominant plasma-phase reactions. In Chapters 2 and 3, the gas-phase dynamics are approximated using a first principles-based model, whereas the latter half of this dissertation relies on a computational fluid dynamics approach. At the microscopic scale, the complex particle interactions that define the growth of a-Si:H thin film layers are tracked using a hybrid kinetic Monte Carlo algorithm. These scales are linked via a dynamic boundary condition which is updated at the completion of each time step. A computationally efficient parallel programming scheme allows for significantly shortened computational times and solutions to previously infeasible system sizes. Transient batch deposition cycles using the aforementioned multiscale model provide new insight into the operation of PECVD systems; spatial non-uniformity in the concentration of SiH3 and H above the substrate surface is recognized as the primary mechanism responsible for non-uniform thin film product thicknesses. Two key modes are identified to address the aforementioned non-uniformity: (1) run-to-run control of the wafer substrate temperature through the adaptation of an exponentially-weighted moving average algorithm, and (2) the design of new CVD geometries which minimize spatial variations in the concentration of deposition species. These efforts have resulted in optimized PECVD showerhead designs and spatial temperature profiles which limit the thin film thickness non-uniformity to within 1% of the product specification.